Media as an Environment of Treats: 15 Years in the Shadow of the Information Security Doctrine - Dzyaloshinskiy, Iosif; Dzyaloshinskaya, Marina (International Review of Management and Marketing, 2015)
This paper presents the results of research devoted to study of the Russians’ attitude to media threats and the ways to minimize the damage caused by them. It is demonstrated that the number of peculiarities of the modern media that are recognized by different publics as threats is significantly less than the register offered by experts and the list of threats provided in the Information Security Doctrine. The weight of evidence suggests that after 15 years of realization of the Information Security Doctrine in a particular country, Russia will again have to return to understanding of the media threats as a global phenomenon requiring the same number of global solutions. And these solutions should be based on not only and rather than prohibitions and punishments but on development of the society of knowledge founded on the humanistic values and four fundamental principles reflected in the UNESCO Constitution: promotion of freedom of expression in traditional and new media including the Internet; availability of quality education for everyone; respect to cultural and language diversity; universal access to information and knowledge, in particular, to the information being a public domain. Keywords: Media, media threats, media security, Information Security Doctrine JEL Classifications: O32; O33; O38; Z13